If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2u-41=-7(u+3)
We move all terms to the left:
-2u-41-(-7(u+3))=0
We calculate terms in parentheses: -(-7(u+3)), so:We get rid of parentheses
-7(u+3)
We multiply parentheses
-7u-21
Back to the equation:
-(-7u-21)
-2u+7u+21-41=0
We add all the numbers together, and all the variables
5u-20=0
We move all terms containing u to the left, all other terms to the right
5u=20
u=20/5
u=4
| 17x+1=18x | | -7(6n-2)=6n+14 | | 3-(4x+8)+10=-x+2(x+10) | | 3t–2=–11 | | 3(n+2)=6+3n | | X=8/5y+7 | | -8(-6+3n)-3n=6(4n+4) | | 6x(x-5)=5(x+5) | | x+4+2x=22 | | 3t–2=-11 | | 8x+2(x-18=11(2x-4)-16 | | 62=5(x+2)+8x | | 7=-4x-1+2x | | 3v−–7=13 | | x/2+3=17-3x | | 8+8r=-8(6-2r) | | 19x+17x-43=-6x+87 | | 1+8n-2=-1 | | -8v+7=15 | | 9.2w-4.16+9.6w=8.9w+13.66 | | 16x–28=22x–65 | | 4n+13=36 | | 21w=120 | | 6+6y=8y-8 | | 5-3a+8=16 | | 3(m+9)=18 | | 6/y-5=8/y+1 | | 2(m+2)=4(m-8) | | 2/3(9 | | −5x−(7−4x)=−2(3x−4) | | -2r+8(3r+3)=7r+39 | | -14=-11a |